Some Educational Problems of Left-Handedness - Tamošaitytė, Irena (Acta Paedagogica Vilnensia, 1991)
This paper analyses the problems faced by left-handed students at school. The problems become especially pronounced when attempts are made to teach a left-handed pupil to write with his right hand. Apart from an inferiority complex of being "unlike all others", converted left-hander usually have disgraphia, i.e., difficulties in learning to write. Some left-handers writing with their right hands write clearly, but very slowly, others – unclearly and unintelligibly. They often confuse letters, write uneven rows, and produce a mirror image, i.e., flip letters and invert the direction of the entire line. The survey of the Vilnius schools revealed that teachers are inclined to abandon the harmful practices of conversion and allow children to choose which hand to write with. However, writing training is often left unattended, because teachers have no special methods of writing teaching. Difficulties arise during the lessons of crafts. Teachers are not able to demonstrate some crafts with a left hand, and so they are unable to teach left-handed students.
Keywords: left-handedness; disgraphia; learning difficulties